The Conditions Governing the Payment of Spousal Maintenance and the Legal and Criminal Enforcement Guarantees Regarding Refusal to Pay Maintenance in the Legal System of Iran and Egypt - Alireza Shekarbeigi; omid emamy (مطالعات تطبیقی حقوق کشورهای اسلامی)
One of the financial obligations arising from cohabitation is the provision of necessary expenses, which are foreseen in the legal systems in the form of alimony. One of the basic sources of rights of any country is the relevant laws of that country, because many of the rights of individuals are specified and determined in the laws of the countries, and it is through referring to the laws that one can determine the extent of the rights of individuals. Since the law of Iran is derived from Sharia, the husband is required to pay alimony to his wife, and his refusal to do so only in cases that are recognized as permissible by mystics and exempts him from the crime of abandoning alimony. Affecting the French law, this issue is observed in Egyptian law, and similar to the penal Code and the Iranian family protection law, a couple who refuses to pay alimony is sentenced to prison. Based on this, considering the many practical similarities in this article, we analyzed the descriptive analysis of cases of inclusion, objection and guarantee of executions and concluded that the only differences are the criteria for determining the amount and duration of imprisonment as a guarantee of execution.